The Caesarean section epidemic: a call for a reduction in the number of Caesarean sections - Anis Cerovac; Damir Ramić; Dubravko Habek; Asmir Aldžić; Ratko Knežević (Medicinski glasnik, 2025)
A caesarean section (CS) is an obstetric surgical intervention and mode of delivery which aims to finish the pregnancy surgically. CS are one of the most important surgical interventions in modern obstetrics and have lead to a significant reduction of fetal and maternal mortality. However, it is important to take into consideration that CS can have risks and lead to unwanted short-term and long-term consequences. One of the main questions of modern obstetric is the ideal CS rate, including ways to reduce an undesirably high CS rate. The ideal CS rate ranging between 10 to 20% according to various research, but some countries have reached rates exceeding 50%, while in other, less developed countries, the issue of accessibility for CS still exists and consequently leads to a high mortality rate. Significant inequality exists in CS accessibility between developed and less developed areas of countries, and countries themselves. In some cases it is even desirable to increase CS rates in order to reduce negative patient outcome.
Keywords: Obsterics; obstetric surgical procedures; prevalence